Perbandingan Efisiensi Aktual Dan Spesifikasi Generator BTG II Power Plant PT. Semen Tonasa 2Ã—35 MW Pada Berbagai Beban Aktual - Usman, Usman; Multazam, Ahmad; Gaffar, Ahmad (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2022)
The efficiency of generators in a power plant decreases as running duration increases. This can also happen to the generator of the PT. Steam Power Plant. The Semen Tonasa Power Plant is also known as the Boiler Turbine Generator (BTG) Power Plant. BTG II has been operating for approximately 8 years and based on generator operation data, there has been a decrease in the power generated by the genera-tor, when viewed from the power input to the current turbine, compared to the initial operation of this plant. The aims of this study are to assess the value of the real generator efficiency and compare it to the efficiency generator based on its specifications. Data loading is required to ascertain the true value of generator efficiency, as the output power created by the generator and the input power is the power gen-erated by the turbine, which is computed using the enthalpy reduction method. According to the research, the average generator efficiency values for generator units C and D are 91.36 percent and 90.34 percent, respectively, with real average loads of 25,56 MW and 25,08 MW. In comparison to the data standards, generator unit C saw a 6.76 percent drop in efficiency, whereas generator unit D experienced a 7.76 per-cent decrease efficiency. Comparison with the data specifications for generator units C experienced a decrease in efficiency of 6,76% while generator unit D experienced a decrease in efficiency of 7,76%. The efficiency of the generator in unit C decreased 0.85% per year, and unit D was 0.97%.